Phenomenological models of residual mechanical properties of polymer composites under fatigue loading: review, analysis of descriptive ability and classification (Fracture and Structural Integrity, 2026)
In this work, a review and mathematical analysis of phenomenological models of residual strength and residual stiffness of polymer composite materials under fatigue loading have been carried out. The methodology of the analysis is described in detail, including various approaches to determining damage based on changes in mechanical properties, as well as the requirements for functions that can be used to describe experimental dependencies. The considered models have been classified according to the characteristic form of their mathematical function: polynomial, power, exponential, logarithmic, and trigonometric models. A distinct category has been established for models utilizing cumulative distribution functions. The possibilities for further development and application of phenomenological models of residual mechanical properties for the improvement of strength analysis approaches for composite structures have been outlined.
Keywords: Polymer composites; Fatigue; Damage; Models of residual mechanical characteristics; Residual strength; Residual stiffness